2009
DOI: 10.1007/s11367-008-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of two baby food packaging alternatives: glass jars vs. plastic pots

Abstract: Background, aim, and scope This paper compares the life cycle assessment (LCA) of two packaging alternatives used for baby food produced by Nestlé: plastic pot and glass jar. The study considers the environmental impacts associated with packaging systems used to provide one baby food meal in France, Spain, and Germany in 2007. In addition, alternate logistical scenarios are considered which are independent of the two packaging options. The 200-g packaging size is selected as the basis for this study. Two other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(89 citation statements)
references
References 11 publications
3
76
0
3
Order By: Relevance
“…These evaluations can be seen in Table V. Similar results have also appeared in the results of a study of baby food jars produced from glass and PET bottles [24]. Humbert et al (2009) reported that plastic containers produced using 14-24% less energy, caused 28-31% less input on global warming, contained 31-34% less respiratory inorganic materials, caused 28-31% less terrestrial acidity and pollution Using of recycled materials (-) [24]. Another work on sustainable packaging have the similar results [25].…”
Section: B Results Of Evaluation Unit Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…These evaluations can be seen in Table V. Similar results have also appeared in the results of a study of baby food jars produced from glass and PET bottles [24]. Humbert et al (2009) reported that plastic containers produced using 14-24% less energy, caused 28-31% less input on global warming, contained 31-34% less respiratory inorganic materials, caused 28-31% less terrestrial acidity and pollution Using of recycled materials (-) [24]. Another work on sustainable packaging have the similar results [25].…”
Section: B Results Of Evaluation Unit Analysissupporting
confidence: 83%
“…Analysis based on packaging clearly shows that PET packaging is produced using much less material and energy than glass packaging, CO 2 emissions are less in transportation of PET and in parallel to that less fuel is consumed during the transportation. These evaluations can be seen in Table V. Similar results have also appeared in the results of a study of baby food jars produced from glass and PET bottles [24]. Humbert et al (2009) reported that plastic containers produced using 14-24% less energy, caused 28-31% less input on global warming, contained 31-34% less respiratory inorganic materials, caused 28-31% less terrestrial acidity and pollution Using of recycled materials (-) [24].…”
Section: B Results Of Evaluation Unit Analysissupporting
confidence: 71%
“…In this study EVA was used as an approximation for EVOH according to Humbert et al (2009), who state that this is a suitable choice because changes in impact evaluation are minimal and under cut-off rules, being EVOH prepared by polymerization of ethylene and vinyl acetate to yield the ethylene vinyl acetate (EVA) copolymer followed by hydrolysis. The study by Hischier (2007) was the source of data for the EVA inventory that includes raw materials and chemicals used for production, transport of materials to manufacturing plant, estimated emissions into air, water from production, estimation of energy demand and infrastructure of the plant.…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…Active food contact material shall comply with the EU regulation (EC No 450/2009), which gives particular attention to the nanomaterials [49]. In accordance with the work of Reig et al [50], to date, only three nanomaterials have been authorised by EFSA (European Food Safety Authority) for food contact application.…”
Section: Nanomaterials For Food Contact Applicationmentioning
confidence: 98%
“…as beverage packaging for hot filling. A study shows that the clay-PLA nanocomposite bottles maintained their shapes after conditioning in the oven of 60 °C, while the pristine PLA bottle got deformed (see Figure 13) [49]. Due to the enhancement in barrier property, one concern about using nanoclay in biopolymer is that it may compromise the material's intrinsic biodegradability.…”
Section: Improvement In Other Propertiesmentioning
confidence: 99%